2022
DOI: 10.1136/bmjopen-2021-054657
|View full text |Cite
|
Sign up to set email alerts
|

Association between retinal markers and cognition in older adults: a systematic review

Abstract: ObjectivesTo appraise the existing literature reporting an association between retinal markers and cognitive impairment in adults aged 65 years and over and to provide directions for future use of retinal scanning as a potential tool for dementia diagnosis.DesignSystematic review of peer-reviewed empirical articles investigating the association of retinal markers in assessing cognitive impairment.Data sourcesThree electronic databases, Medline, PsycINFO and EMBASE were searched from inception until March 2022.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…MoCA, as a general cognitive screening tool, correlated with RNFL thickness in our study. Previous reports (Oktem et al, 2015;Liu et al, 2019;Jeevakumar et al, 2022) have shown a significant correlation between OCT parameters and MoCA scores. Our findings suggest that thinner RNFL may indicate reduced MoCA scores which are in line with previous reports.…”
Section: Discussionmentioning
confidence: 69%
“…MoCA, as a general cognitive screening tool, correlated with RNFL thickness in our study. Previous reports (Oktem et al, 2015;Liu et al, 2019;Jeevakumar et al, 2022) have shown a significant correlation between OCT parameters and MoCA scores. Our findings suggest that thinner RNFL may indicate reduced MoCA scores which are in line with previous reports.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, studies exploring the associations between retinal layers and cognitive function in young populations are very scarce. Indeed, the previous studies that have explored these associations were mainly conducted among adults (over 40 years) (Girbardt et al, 2021; Jeevakumar et al, 2022; Khawaja et al, 2016; Ko et al, 2018; Merten et al, 2020). To our knowledge, only one previous study in this field has included young people, showing that retinal layer thickness assessed in middle age was associated with cognitive performance in childhood and adulthood (Barrett‐Young et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies exploring the associations between retinal layers and cognitive function in young populations are very scarce. Indeed, the previous studies that have explored these associations were mainly conducted among adults (over 40 years) (Girbardt et al, 2021;Jeevakumar et al, 2022;Khawaja et al, 2016;Ko et al, 2018;Merten et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that individuals with AD possess considerably thinner retinas than both healthy controls and individuals with mild cognitive impairment [ 32 , 33 , 34 ]. The literature consistently describes thinning of the peripapillary retinal nerve fiber layer (RNFL) and the ganglion cell–inner plexiform layer complex (GC-IPL), along with a reduction in total macular volume in patients with AD [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. A 2017 meta-analysis by den Haan et al reviewed 25 studies analyzing retinal thickness in AD, mild cognitive impairment (MCI) patients and healthy controls (HCs).…”
Section: Ocular Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%